L’Halys chez Hérodote - Kevin Leloux (Studia Hercynia, 2017)
This paper analyses the Halys River description made by Herodotus in his Histories. This study focuses on the several references made by the Father of History in his work. It will examine the part the river took in his vision of the politic, ethnic and geographic state in the historian’s mind and the problems that arise by this presentation. Finally, this article will demonstrate that every crossing of the Halys River made by the Barbarians were a bad omen for the Greeks of Asia Minor and in Greece itself.